INFLUENCE OF COUNTRY OF ORIGIN, BRAND IMAGE, AND PERCEIVED QUALITY ON INTEREST IN BUYING NMAX BRAND MOTORS IN PONOROGO (CASE STUDY OF PONOROGO DISTRICT COMMUNITY) - Ndini, Nofita Krisna; Setyawan, Fery; Widhianingrum, Wahna (Proceeding of International Conference on Social Science and Humanity, 2024)
General Background: In the competitive motorcycle industry, factors such as Country of Origin (COO), Brand Image, and Perceived Quality significantly influence consumer purchasing decisions. Specific Background: Understanding the influence of these factors on consumer interest, particularly for popular models like the Yamaha NMAX, is crucial for effective marketing strategies in specific regions such as Ponorogo. Knowledge Gap: However, limited research has been conducted to explore the simultaneous effects of these variables on consumer purchasing interest, especially in less urbanized areas like Ponorogo, where consumer preferences may differ from urban centers. Aims: This study aims to analyze the influence of COO, Brand Image, and Perceived Quality on the interest in purchasing Yamaha NMAX motorcycles in Ponorogo, both individually and collectively. Results: The findings indicate that while COO has a statistically significant influence, the relationship is negative, suggesting that other factors outweigh the impact of COO in shaping purchase interest. Conversely, Brand Image and Perceived Quality both exhibit positive and significant effects on consumer interest, highlighting their roles as critical determinants in the purchasing decision process. Novelty: The study's novelty lies in its exploration of these variables in a less-studied, regional context, providing new insights into consumer behavior outside major urban centers. Implications: The results suggest that marketing strategies for Yamaha NMAX in Ponorogo should prioritize enhancing Brand Image and Perceived Quality rather than emphasizing COO, as these factors are more influential in driving purchase interest. These findings contribute to a nuanced understanding of regional consumer behavior, which can inform targeted marketing efforts and product positioning in similar contexts.